The role of faculty members in the official Jordanian universities in enhancing academic integrity from their own perspective - AL-Momani, Taghreed Radwan (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the role of faculty members in public Jordanian universities in enhancing academic integrity from their own perspective, and its relationship to some variables, the study used the descriptive approach and relied on the questionnaire that was applied to a sample of (300) faculty members from the universities members at the University of Jordan, Yarmouk University and Hashemite University, were chosen by a random stratified way, and the results of the study showed that the role of faculty members in public Jordanian universities in enhancing academic integrity from their own perspective, came in moderate level)3.36/5)and the results of the study showed the presence of statistical significant difference in changing faculty members attributed to the variable type The college and scientific advice, and the absence of an effect for the academic rank variable, and According to the results, The study recommended the necessity of enhancing integrity of the employees and spreading awareness among them.
Keywords: The role of faculty members; Academic integrity; Public Jordanian Universities